SEVERE ACUTE RESPIRATORY SYNDROME AND ITS EFFECTS ON HEALTH CARE - Farley, Margaret; Socha, Linda (Operating Room Nurses Association of Canada Journal, 2005)
The global epidemic of severe acute respiratory syndrome (SARS) indirectly has affected all health care facilities in affected nations and has unaffected nations on alert. Health care practitioners need to be aware of infection control measures to prevent the spread of SARS. This article looks at this new disease and how it has affected the delivery of health care in Canada. Surgical suites worldwide embrace progress in technology and new surgical techniques daily. Nurses, however, often forget about the impact that discovery of a new disease could have on nursing practice. It is important to minimize the risks of such a discovery for health care providers as well as patients, family members, friends, and the world population in general.